It's all in the music: A systematic review on the effects of musical characteristics on participants' experience and behavior during leisure activities. - Céline Daelemans; Casper Bonapart; Adriana Leni Smit; Inge Stegeman (PLoS ONE)
Background Excessively loud music is frequently played at leisure activities, posing significant health risks. However, the lack of consensus on consumers' preferred music settings makes it difficult to implement preventive measures against high noise levels. Therefore, our objective is to systematically evaluate how different musical characteristics influence the experiences and behaviors of individuals engaged in leisure activities. Methods We conducted a search for studies examining the effects of musical characteristics on individuals at leisure activities where the musical experience is of primary focus. The search was performed using the Medline Pubmed, Embase Elsevier, Cochrane, PsychInfo, and ClinicalTrial.gov databases. The exclusion criteria included: leisure activities related to sports, studies evaluating music as a treatment, lab settings, case studies, and participants below 15 years old. The NOS, RoB2, and ROBINS-I tools were used to assess risk of bias. Results relevant to our outcomes of interest were extracted and summarized in tables. Results We identified 2503 studies, of which 37 studies were included for data extraction. The total number of participants in this systematic review was 16843. Among the 37 studies, 23 were observational with the remainder being experimental control trials. Risk of bias in the studies was high. Our findings indicate that musical characteristics such as low frequencies, high groove, high tempo, and live performance enhanced participants' movements and emotions. Excessively high levels, such as those found in nightclubs, were deemed unnecessary by those exposed. These extreme volumes also caused discomfort and posed a risk to hearing health. Interpretation The high risk of bias makes it difficult to draw conclusions based on the data in this systematic review. Therefore, and in order to inform policy makers, we need adequate randomized controlled trials in order to assess the effects of different levels of loudness on music experience. Registration: PROSPERO registration: CRD42023412634.